Aerothermodynamics of aircraft engine components - Oates, Gordon C. (American Institute of Aeronautics and Astronautics, 1985)
Annotation Design and R & D engineers and students will value the comprehensive, meticulous coverage in this volume. Beginning with the basic principles and concepts of aeropropulsion combustion, chapters explore specific processes, limitations, and analytical methods as they bear on component design.
Keywords: Aerothermodynamics.; Aircraft gas-turbines.; elektronické knihy; electronic books